2019
DOI: 10.4028/www.scientific.net/jnanor.60.63
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Fluorine and Cobalt Co-Doped Tin Oxide Thin Films Deposited by Chemical Spray Pyrolysis

Abstract: Transparent conducting Cobalt-fluorine co-doped tin oxide (SnO2: (Co, F)) thin filmswere deposited onto preheated glass substrates using the chemical spray pyrolysis method. The ([Co2+]/[Sn4+]) atomic concentration ratio (y)in the spray solution was varied between 0 and 5 at. %. The structural, electrical, optical and photoluminescence properties of these films were studied. It is found that the thin films are polycrystalline with a tetragonal crystal structure corresponding to SnO2 phase having a preferred or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…where k = 0.94 is the shape factor, λ is the wavelength of CuKα radiation source (λ = 1.5406 Ǻ), β is the (full width half maxi-mum) FWHM value of the respective diffraction peak, and θ is the Bragg angle. The crystallite size values of Co doped SnS 2 thin films are lower than that of pure SnS 2 even with the change of substrate temperature [32]. Because Sn 2+ has a bigger ionic radius then Co 2+ .…”
Section: Structural Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…where k = 0.94 is the shape factor, λ is the wavelength of CuKα radiation source (λ = 1.5406 Ǻ), β is the (full width half maxi-mum) FWHM value of the respective diffraction peak, and θ is the Bragg angle. The crystallite size values of Co doped SnS 2 thin films are lower than that of pure SnS 2 even with the change of substrate temperature [32]. Because Sn 2+ has a bigger ionic radius then Co 2+ .…”
Section: Structural Studiesmentioning
confidence: 89%
“…Hexagonal structure remains stable for SnS 2 whatever the temperature change, it is a layered material with a cadmium iodide (CdI2) type structure [2]. Thereafter, tin sulfide exists in several phases such as SnS, SnS 2 Sn 2 S 3 and Sn 3 S 4 lead to bonding characteristics of tin and sulfur, only at higher temperatures (upper to 350° C) the SnS 2 phase appear [32]. It has an n-type conductivity with a wide optical band gap varying between 2.40 and 2.88 eV [3,4], a light absorber (absorption coefficient up to 10 4 cm -1 ) and relatively high charge carrier mobility in the range of 18.3 to 230 cm 2 /V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that SnO 2 : Co films prepared by sol-gel method had a higher carrier concentration and mobility than undoped SnO 2 films, resulting in improved electrical conductivity. The films also showed enhanced visible light absorption and photocatalytic activity [111]. Alloying zinc oxide (ZnO) with copper (Cu) has been shown to improve its electrical and optical properties.…”
Section: Strategies For Improving the Electrical And Optical Properti...mentioning
confidence: 99%
“…Each SnO2 cell contains two Sn atoms and four O atoms with a space group of p42/mnm (No. 134), lattice constants a=b=0.4737 nm, c=0.3186 nm, and α=β=γ=90° [22][23]. The SnO2 crystal anion coordination number is 6:3, and each Sn ion is adjacent to six oxygen ions, and each oxygen ion is adjacent to 3 tin ions adjacent.…”
Section: Lattice Model Buildingmentioning
confidence: 99%